2023
DOI: 10.1007/s11547-023-01593-x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of machine learning-based radiomics approach for predicting microsatellite instability status in colorectal cancer

Abstract: This study aimed to systematically summarize the performance of the machine learning-based radiomics models in the prediction of microsatellite instability (MSI) in patients with colorectal cancer (CRC). It was conducted according to the preferred reporting items for a systematic review and meta-analysis of diagnostic test accuracy studies (PRISMA-DTA) guideline and was registered at the PROSPERO website with an identifier CRD42022295787. Systematic literature searching was conducted in databases of PubMed, Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…AI applied to radiologic images, called radiomics, was also evaluated to predict the MSI status in colorectal cancer with no exploration of BRAF and KRAS mutation status [ 51 ]. Contrary to pathomics, whole images in radiomics are smaller and consequently less informative but can be entirely used without preprocessing to train algorithms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AI applied to radiologic images, called radiomics, was also evaluated to predict the MSI status in colorectal cancer with no exploration of BRAF and KRAS mutation status [ 51 ]. Contrary to pathomics, whole images in radiomics are smaller and consequently less informative but can be entirely used without preprocessing to train algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to pathomics, whole images in radiomics are smaller and consequently less informative but can be entirely used without preprocessing to train algorithms. Recent retrospective studies on the subject showed an AUC with a range from 0.78 to 0.96 AUC [ 51 ]. Some studies combined imaging with clinical and/or histological data (Ki-67, gender, age, tumor localization, differentiation degree of tumor, smoking history, hypertension, diabetes, and family history of cancer), allowing a better prediction of the MSI status [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, information on MSI expression status obtained postoperatively has limited impact on treatment planning prior to surgery. Moreover, the limited samples obtained through biopsy may not comprehensively reflect tumor heterogeneity, leading to false-negative results (2.1–5.9%) [ 16 , 17 ]. Additionally, biopsies and surgeries are invasive, time-consuming, expensive, and carry risks of complications, making repeated monitoring inconvenient [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the limited samples obtained through biopsy may not comprehensively reflect tumor heterogeneity, leading to false-negative results (2.1–5.9%) [ 16 , 17 ]. Additionally, biopsies and surgeries are invasive, time-consuming, expensive, and carry risks of complications, making repeated monitoring inconvenient [ 17 ]. Hence, there is an urgent need to develop a non-invasive, reliable, and cost-effective method to identify MSI status.…”
Section: Introductionmentioning
confidence: 99%
“…Medical images contain a large amount of invisible data, and it is the value of radiomics to reveal these invisible disease features. Radiomics has been defined as the use of mathematical algorithms to transform the underlying pathophysiological information contained in medical images into quantitative, high-dimensional image features and to explore the correlation of these image features with clinical outcomes or biological properties ( 6 , 7 ). When radiomics is applied to cancer research, it is possible to characterize the imaging of tumor patients non-invasively, quantify the heterogeneity between tissues, describe the microenvironment of the tumor, assess the effectiveness of treatment, and predict survival after obtaining radiological images by CT, MRI, and other examination methods ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%